Scientific Publication and Evaluation of Sustainable Teacher Professional Development: Research in Madrasah Aliyah Metro City - Iswati, Iswati; Pahrudin, Agus; Syafril, Syafrimen; Koderi, Koderi (Jurnal Penelitian Pendidikan Islam, 2023)
The paper aims to examine the significance of teachers' ongoing professional development in the realm of scientific publications at Madrasah Aliyah in Metro City, as an indication of their dedication to enhancing the standard of education. The researcher employed a comprehensive technique to evaluate the surrounding circumstances of teachers' continuous professional growth when designing the research methodology. Information was acquired via interviews, observation, and examination of pertinent documents. Data sources encompass input from educators, school administrators, and pertinent records pertaining to professional growth and training. Data analysis approaches, such as classification, synthesis, and mapping, are used to get a thorough grasp of the context of teacher professional development in the field of scientific publications. The research findings indicate that the state of teachers' ongoing professional growth in the area of scientific publications at Madrasah Aliyah Metro City is still confronted with several obstacles. Teacher participation rates typically exhibit a tendency towards being insufficient, primarily due to obstacles such as limited time availability and inadequate backing from educational institutions. This research formulates solutions to enhance teacher participation by comprehending the underlying cause of the problem. In order to foster the ongoing professional development of instructors in the field of scientific publications, it is anticipated that a comprehensive strategy, which includes capacity building and proactive institutional assistance, would be implemented to establish a favorable environment. This result emphasizes the significance of enhancing policies and providing targeted incentives to promote and motivate teachers to enhance their involvement in scientific publication endeavors.